A polyphenylene sulfide composite material and preparation method thereof

By introducing core-shell structure toughening agent into the polyphenylene sulfide composite material to form a tough network structure, the problems of poor toughness and low impact strength of polyphenylene sulfide are solved, and the impact strength of the material is significantly improved.

CN116004010BActive Publication Date: 2025-03-04上海冷盟精密电机有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211729693.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-03-04
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

Polyphenylene sulfide has poor toughness and low impact strength, which limits its application in the fields of automotive lightweight and new energy vehicles.

Method used

Composite materials containing polyphenylene sulfide, glass fiber and core-shell structural toughener are used. The core-shell structure toughener is made from modified and blended with modified carbon nanotubes and low-density polyethylene by end-alkenyl silane coupling agents to form a tough network structure to enhance the impact strength of the material.

Benefits of technology

By forming a tough network structure, the impact strength of the polyphenylene sulfide composite material is improved, and the problems of poor toughness and low impact strength are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of polymer materials, and specifically discloses a polyphenylene sulfide composite material and a preparation method thereof. A polyphenylene sulfide composite material is composed of the following raw materials in parts by weight: 40-75 parts of polyphenylene sulfide, 15-30 parts of glass fiber, and 3-10 parts of toughening agent; the toughening agent is a core-shell structure, with modified carbon nanotubes as the core and low-density polyethylene as the shell; the preparation method of the toughening agent comprises the following steps: using a terminal olefinic silane coupling agent to modify hydroxylated carbon nanotubes to obtain modified carbon nanotubes, and the mass ratio of the terminal olefinic silane coupling agent to the hydroxylated carbon nanotubes is 1: (0.8-1.5); low-density polyethylene and modified carbon nanotubes are mixed, melted, extruded, and injection molded in a mass ratio of (2-5): 1 to obtain a toughening agent. A polyphenylene sulfide composite material prepared in the present application has the advantages of good toughness and high impact strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and more specifically, to a polyphenylene sulfide composite material and a preparation method thereof. Background Art

[0002] Polyphenylene sulfide (PPS), also known as polyphenylene sulfide and poly(sub)phenylene sulfide, is recognized as the sixth largest engineering plastic and the first special engineering plastic after polyamide (PA), polyoxymethylene (POM), polycarbonate (PC), polyphenylene ether (PPO) and polybutylene terephthalate (PBT).

[0003] Polyphenylene sulfide is a white or nearly white, easy to crystallize, hard and brittle polymer composed of alternating benzene rings and sulfur atoms. A large number of benzene rings increase the rigidity of polyphenylene sulfide, making it more brittle, less tough, and with low impact strength. This limits the application of polyphenylene sulfide to a certain extent. With the development of lightweight automobiles and the popularization of new energy vehicles, more and more traditional auto parts and new energy battery manufacturers will choose high-performance special engineering plastics as raw materials for their products, which puts higher requirements on special engineering plastics, especially polyphenylene sulfide with higher cost performance.

[0004] Therefore, improving the impact strength of polyphenylene sulfide is of great significance for its better use in the market in the future. Summary of the invention

[0005] In order to solve the problem that polyphenylene sulfide has poor toughness and low impact strength, the present application provides a polyphenylene sulfide composite material and a preparation method thereof.

[0006] In a first aspect, the present application provides a polyphenylene sulfide composite material, which adopts the following technical solution:

[0007] A polyphenylene sulfide composite material, comprising the following raw materials in parts by weight: 40-75 parts of polyphenylene sulfide, 15-30 parts of glass fiber, and 3-10 parts of a toughening agent;

[0008] The toughening agent is a core-shell structure, with modified carbon nanotubes as the core and low-density polyethylene as the shell;

[0009] The preparation method of the toughening agent comprises the following steps:

[0010] The hydroxylated carbon nanotubes are modified by using a terminal olefinic silane coupling agent to obtain modified carbon nanotubes, wherein the mass ratio of the terminal olefinic silane coupling agent to the hydroxylated carbon nanotubes is 1:(0.6-0.85); low-density polyethylene and the modified carbon nanotubes are mixed, melted and extruded in a mass ratio of (2-5):1 to obtain a toughening agent.

[0011] By adopting the above technical scheme, the toughening agent prepared by the above preparation method is used, the terminal olefinic silane coupling agent is grafted on the surface of the modified carbon nanotube, the modified carbon nanotube and the low-density polyethylene are melt-blended, the low-density polyethylene macromolecular chain reacts and cross-links with the terminal olefinic silane coupling agent on the surface of the modified carbon nanotube to form a tough network structure, and the low-density polyethylene macromolecular chain is coated on the surface of the modified carbon nanotube to form a core-shell structure with the modified carbon nanotube as the core and the low-density polyethylene as the shell; the toughening agent of the core-shell structure is mixed with glass fiber and polyphenylene sulfide to obtain a polyphenylene sulfide composite material. When the material is subjected to external impact, on the one hand, the core-shell structure The modified carbon nanotubes in the core-shell structure will first undergo relative slip, and the core-shell structure will deform before the polyphenylene sulfide matrix. The silver streaks caused by this deformation can be terminated in time by the flexible interface of the core-shell structure shell, absorbing energy and improving the impact strength of the polyphenylene sulfide composite material. On the other hand, the low-density polyethylene macromolecular chains on the surface of the toughening agent are entangled with polyphenylene sulfide and glass fiber molecules to form a tough network structure, and the modified carbon nanotubes act as skeleton connection points in it, forming a stronger interface effect, which further improves the impact strength of the polyphenylene sulfide composite material, thereby solving the problem of poor toughness and low impact strength of polyphenylene sulfide.

[0012] Preferably, the mass ratio of the terminal olefinic silane coupling agent to the hydroxylated carbon nanotubes is 1:(0.7-0.8).

[0013] By adopting the above technical scheme, when the mass ratio of the terminal alkenyl silane coupling agent to the hydroxylated carbon nanotube is 1:(0.7-0.8), the amount of the alkenyl silane coupling agent is moderate, the amount of the terminal alkenyl silane coupling agent grafted on the surface of the hydroxylated carbon nanotube is moderate, the amount of the low-density polyethylene grafted on the surface of the modified carbon nanotube is moderate, the size of the generated core-shell structure is moderate, the effective contact area between the toughening agent and the polyphenylene sulfide is moderate, and when the polyphenylene sulfide composite material is subjected to external impact, it can effectively transfer energy to the modified carbon nanotubes, thereby absorbing more energy and improving the impact strength of the polyphenylene sulfide.

[0014] Preferably, the weight portion of the toughening agent is 5-7 parts.

[0015] Preferably, the composition further comprises 3-8 parts by weight of amino-terminated hyperbranched polyamide and 0.5-1.4 parts by weight of a compatibilizer, wherein the compatibilizer is glycerol tri(1,2-epoxy)propyl ether and / or polyepoxy silicone oil.

[0016] By adopting the above technical scheme, the compatibilizer contains multiple epoxy groups, and the epoxy groups can react with the -SH groups on the polyphenylene sulfide and the active groups such as the amino groups on the amino-terminated hyperbranched polyamide, so that the compatibility between the amino-terminated hyperbranched polyamide and the polyphenylene sulfide is significantly improved, and the interface bonding performance between the two is improved; the active groups such as the amino groups on the amino-terminated hyperbranched polyamide can also be cross-linked with the active groups on the glass fiber, so that the polyphenylene sulfide, the glass fiber, the toughening agent and the amino-terminated hyperbranched polyamide all have good compatibility; the amino-terminated hyperbranched polyamide has good toughness and high impact strength due to its special hyperbranched structure, and is mixed with the polyphenylene sulfide, the glass fiber and the toughening agent under the action of the compatibilizer, thereby improving the impact strength of the polyphenylene sulfide.

[0017] Preferably, the weight portion of the compatibilizer is 0.7-1 part.

[0018] Preferably, the compatibilizer is polyepoxy silicone oil.

[0019] By adopting the above technical scheme, the polyepoxy silicone oil not only contains multiple epoxy groups, which can improve the compatibility between terminal amino hyperbranched polyamide and polyphenylene sulfide, but also has flexible segments. The flexible segments are entangled with other macromolecular segments, further improving the impact strength of polyphenylene sulfide.

[0020] Preferably, the glass fiber is modified by a terminal epoxy silane coupling agent to obtain a modified glass fiber; the mass ratio of the terminal epoxy silane coupling agent to the glass fiber is (0.03-0.08):1.

[0021] By adopting the above technical solution, the compatibility between the glass fiber treated with the terminal epoxy silane coupling agent and the polyphenylene sulfide is better, and the toughening effect of the glass fiber is better.

[0022] Preferably, the epoxy-terminated silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0023] In a second aspect, the present application provides a method for preparing a polyphenylene sulfide composite material, using the following technical solution: A method for preparing a polyphenylene sulfide composite material, comprising the following steps:

[0024] The polyphenylene sulfide, glass fiber, toughening agent, amino-terminated hyperbranched polyamide and compatibilizer are mixed, melt-extruded and granulated to obtain a polyphenylene sulfide composite material.

[0025] In summary, this application has the following beneficial effects:

[0026] 1. The present application uses a terminal olefinic silane coupling agent to modify hydroxylated carbon nanotubes to obtain modified carbon nanotubes with terminal olefinic silane coupling agents grafted on the surface. The modified carbon nanotubes are then melt-blended with low-density polyethylene so that the low-density polyethylene macromolecular chains are coated on the surface of the modified carbon nanotubes to obtain a toughening agent with a core-shell structure.

[0027] A core-shell structure toughening agent is mixed with glass fiber and polyphenylene sulfide to prepare a polyphenylene sulfide composite material. When the material is impacted, on the one hand, the modified carbon nanotubes inside the core-shell structure will first undergo relative slip, and the core-shell structure will deform before the polyphenylene sulfide matrix. The silver streaks caused by this deformation can be terminated in time by the flexible interface of the core-shell structure shell, absorbing energy and improving the impact strength of the polyphenylene sulfide composite material; on the other hand, the low-density polyethylene macromolecular chains on the surface of the toughening agent are entangled with the polyphenylene sulfide and glass fiber molecules; the terminal olefin silane coupling agent on the modified carbon nanotubes cross-links with the low-density polyethylene, so that the interior of the core-shell structure and the interface bonding are both tough network structures, so that the interface bonding performance between the toughening agent, polyphenylene sulfide and glass fiber molecules is better, and the modified carbon nanotubes play the role of skeleton connection points, further improving the impact strength of the polyphenylene sulfide composite material, thereby solving the problem of poor toughness and low impact strength of polyphenylene sulfide.

[0028] 2. The raw materials of the present application also include amino-terminated hyperbranched polyamide and a compatibilizer. The amino-terminated hyperbranched polyamide has good toughness due to its hyperbranched structure. The compatibilizer can make the amino-terminated hyperbranched polyamide and polyphenylene sulfide have good interface bonding properties. Under the action of the compatibilizer, the amino-terminated hyperbranched polyamide can improve the impact strength of polyphenylene sulfide.

[0029] 3. The present application prefers polyepoxy silicone oil as a compatibilizer. Polyepoxy silicone oil can not only improve the compatibility between terminal amino hyperbranched polyamide and polyphenylene sulfide, but also introduce flexible segments into the system. These flexible segments are entangled with other macromolecular segments, further improving the impact strength of polyphenylene sulfide. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with embodiments.

[0031] Table 1. Raw material specifications

[0032]

[0033] Preparation example of toughening agent

[0034] Preparation Example 1

[0035] The toughening agent is prepared according to the following steps:

[0036] 10 kg of terminal olefin silane coupling agent γ-(methacryloyloxy)propyltrimethoxysilane was mixed with 50 kg of water, 6 kg of hydroxylated carbon nanotubes were added, and the mixture was stirred in a 45° C. water bath for 10 h, filtered, washed, and dried to obtain modified carbon nanotubes;

[0037] 2 g of dicumyl peroxide was mixed with 100 g of acetone, and then 2 kg of low-density polyethylene was added and mixed, and the acetone was evaporated under reduced pressure, and 1 kg of modified carbon nanotubes was added, mixed, melted, and extruded to obtain a toughening agent.

[0038] Preparation Example 2-4

[0039] The toughening agent is different from that in Preparation Example 1 in that the raw material composition of the toughening agent is different, and the specific composition is shown in Table 2 below:

[0040] Table 2. Raw material composition of toughening agent

[0041]

[0042] Comparative Example of Preparation of Toughening Agent

[0043] Preparation Comparative Example 1-2

[0044] The toughening agent is different from the preparation example 1 in that the raw material composition of the toughening agent is different. The specific composition is shown in Table 3 below.

[0045] Table 3. Raw material composition of toughening agent

[0046]

[0047] Preparation Example of Polyepoxy Silicone Oil

[0048] Preparation Example a

[0049] Polyepoxy silicone oil is prepared according to the following steps:

[0050] 0.5 kg of allyl glycidyl ether was mixed with 2 kg of hydrogen-containing silicone oil, 0.8 g of platinum catalyst was added, the mixture was mixed and stirred, the temperature was raised to 95° C., and the mixture was kept warm for 5 hours to obtain polyepoxy silicone oil.

[0051] Preparation example of modified glass fiber

[0052] Preparation Example A

[0053] The modified glass fiber is prepared according to the following steps:

[0054] 0.3 kg of terminal epoxy silane coupling agent γ-glycidyloxypropyltrimethoxysilane was mixed with 10 kg of 30% by volume ethanol aqueous solution, 10 kg of glass fiber was added, stirred at 75° C. for 20 minutes, and dried to obtain modified glass fiber.

[0055] Preparation Example B

[0056] The modified glass fiber is different from Preparation Example A in that the mass of the terminal epoxy silane coupling agent is different. The mass of the terminal epoxy silane coupling agent in this Preparation Example is 0.8 kg.

[0057] Example

[0058] Example 1

[0059] A polyphenylene sulfide composite material, the formula of which is as follows:

[0060] 4kg of polyphenylene sulfide, 1.5kg of glass fiber, and 0.3kg of the toughening agent prepared in Preparation Example 1;

[0061] A polyphenylene sulfide composite material is prepared according to the following steps:

[0062] The polyphenylene sulfide, glass fiber and toughening agent are mixed, melt-extruded and granulated to obtain a polyphenylene sulfide composite material.

[0063] Embodiment 2-4

[0064] A polyphenylene sulfide composite material, which is different from Example 1 in that the raw material composition of the polyphenylene sulfide composite material is different, and the specific composition is shown in Table 4 below:

[0065] Table 4. Raw material composition of polyphenylene sulfide composites

[0066] project Polyphenylene sulfide (kg) Glass fiber(kg) Toughening agent (kg) Example 1 4 1.5 0.3 Example 2 7.5 3 1 Example 3 6 2.6 0.5 Example 4 6 2.6 0.7

[0067] Example 5

[0068] A polyphenylene sulfide composite material is different from Example 1 in that the toughening agent is different. This example selects the toughening agent prepared in Preparation Example 2.

[0069] Example 6

[0070] A polyphenylene sulfide composite material is different from Example 1 in that the toughening agent is different. This example selects the toughening agent prepared in Preparation Example 3.

[0071] Example 7

[0072] A polyphenylene sulfide composite material is different from Example 1 in that the toughening agent is different. This example selects the toughening agent prepared in Preparation Example 4.

[0073] Example 8

[0074] A polyphenylene sulfide composite material is different from Example 1 in that 0.3 kg of amino-terminated hyperbranched polyamide and 0.05 kg of compatibilizer glycerol tri(1,2-epoxy)propyl ether are newly added to the raw materials of the polyphenylene sulfide composite material.

[0075] Example 9

[0076] A polyphenylene sulfide composite material is different from Example 1 in that 0.8 kg of amino-terminated hyperbranched polyamide and 0.14 kg of compatibilizer glycerol tri(1,2-epoxy)propyl ether are newly added to the raw materials of the polyphenylene sulfide composite material.

[0077] Example 10

[0078] A polyphenylene sulfide composite material is different from Example 1 in that 0.8 kg of amino-terminated hyperbranched polyamide and 0.14 kg of compatibilizer polyepoxy silicone oil are newly added to the raw materials of the polyphenylene sulfide composite material.

[0079] Embodiment 11

[0080] A polyphenylene sulfide composite material is different from Example 1 in that 0.8 kg of amino-terminated hyperbranched polyamide and 0.07 kg of compatibilizer polyepoxy silicone oil are newly added to the raw materials of the polyphenylene sulfide composite material.

[0081] Example 12

[0082] A polyphenylene sulfide composite material is different from Example 1 in that 0.8 kg of amino-terminated hyperbranched polyamide and 0.1 kg of compatibilizer polyepoxy silicone oil are added to the raw materials of the polyphenylene sulfide composite material.

[0083] Embodiment 13

[0084] A polyphenylene sulfide composite material is different from Example 1 in that 0.8 kg of amino-terminated hyperbranched polyamide, 0.05 kg of compatibilizer polyepoxy silicone oil and 0.05 kg of compatibilizer glycerol tri(1,2-epoxy)propyl ether are newly added to the raw materials of the polyphenylene sulfide composite material.

[0085] Embodiment 14

[0086] A polyphenylene sulfide composite material is different from Example 1 in that the glass fiber is selected differently. In this example, the glass fiber of equal quality is replaced with the modified glass fiber obtained in Preparation Example A.

[0087] Embodiment 15

[0088] A polyphenylene sulfide composite material is different from Example 1 in that the glass fiber is selected differently. In this example, the glass fiber is replaced with the modified glass fiber obtained in Preparation Example B.

[0089] Comparative Example

[0090] Comparative Example 1

[0091] A polyphenylene sulfide composite material is different from Example 1 in that the toughening agent is different. In this comparative example, the toughening agent prepared in Preparation Example 1 is replaced with the toughening agent prepared in Preparation Comparative Example 1.

[0092] Comparative Example 2

[0093] A polyphenylene sulfide composite material is different from Example 1 in that the toughening agent is selected differently. In this comparative example, the toughening agent prepared in Preparation Example 1 is replaced with the toughening agent prepared in Preparation Comparative Example 2.

[0094] Comparative Example 3

[0095] A polyphenylene sulfide composite material is different from Example 1 in that the toughening agent is different. In this comparative example, the toughening agent prepared in Preparation Example 1 is replaced with the modified carbon nanotubes prepared in Preparation Example 1.

[0096] Detection Methods

[0097] Referring to GB / T1043.1-2008, the impact strength test was performed on the polyphenylene sulfide composite material prepared in Examples 1-15 and Comparative Examples 1-3. The specific test structure is shown in Table 5 below:

[0098] Referring to GB1040-79, a tensile strength test was performed on a polyphenylene sulfide composite material obtained in Example 1-15 and Comparative Example 1-3. The specific test structure is shown in Table 5 below:

[0099] Test results

[0100] Table 5. Performance test of polyphenylene sulfide composite materials

[0101]

[0102]

[0103] It can be seen from Table 5 that the tensile strength of the polyphenylene sulfide composite material prepared in the embodiment of the present application is ≥152MPa and the impact strength is ≥12.1KJ / m 2 , polyphenylene sulfide composite materials have higher tensile strength, higher impact strength and better toughness.

[0104] Combining Example 1 and Comparative Example 1 and Table 5, it can be seen that the impact strength of the polyphenylene sulfide composite material prepared in Example 1 is much higher than that of Comparative Example 1. This may be because: in the toughening agent used in Comparative Example 1, the mass ratio of the terminal olefinic silane coupling agent to the hydroxylated carbon nanotubes is higher than 1:0.85, the content of the terminal olefinic silane coupling agent is too high, a large number of free radicals induce crosslinking or breakage of the low-density polyethylene, and the modified carbon nanotubes are difficult to enter the low-density polyethylene phase, and an effective core-shell structure cannot be formed. The excess terminal olefinic silane coupling agent also reduces the active groups on the surface of the hydroxylated carbon nanotubes, reducing the interface bonding strength between the carbon nanotubes and the polyphenylene sulfide. Therefore, the impact strength of the obtained polyphenylene sulfide composite material is relatively low.

[0105] Combining Example 1 and Comparative Example 2 and Table 5, it can be seen that the impact strength of the polyphenylene sulfide composite material prepared in Example 1 is much higher than that of Comparative Example 2. This may be because: in the toughening agent used in Comparative Example 2, the mass ratio of the terminal silane coupling agent to the hydroxylated carbon nanotube is lower than 1:0.6, the content of the terminal silane coupling agent on the surface of the modified carbon nanotube is too small, and the opportunity to contact with the low-density polyethylene is small. The low-density polyethylene is difficult to coat and graft the modified carbon nanotubes, and the toughness of the formed core-shell structure is poor, and the effective contact area with the polyphenylene sulfide is also small. When the material is subjected to external impact, it cannot transfer energy well to the modified carbon nanotubes inside the core-shell structure, resulting in a low impact strength of the polyphenylene sulfide composite material.

[0106] Combining Example 1 and Comparative Example 3 and Table 5, it can be seen that the impact strength of the polyphenylene sulfide composite material prepared in Example 1 is much higher than that of Comparative Example 3. This may be because: the toughening agent used in Example 1 has a core-shell structure, and the toughening agent with the core-shell structure is mixed with glass fiber and polyphenylene sulfide to prepare the polyphenylene sulfide composite material. When the material is impacted, on the one hand, the modified carbon nanotubes inside the core-shell structure will first undergo relative slip, and the core-shell structure will deform before the polyphenylene sulfide matrix. The silver streaks caused by this deformation can be terminated in time by the flexible interface of the core-shell structure shell, absorbing energy and improving the polyphenylene sulfide composite material. On the other hand, the low-density polyethylene macromolecular chains on the surface of the toughening agent are entangled with polyphenylene sulfide and glass fiber molecules; the terminal olefinic silane coupling agent on the modified carbon nanotubes cross-links with the low-density polyethylene, so that the interior of the core-shell structure and the interface bonding part present a tough network structure, which makes the interface bonding performance between the toughening agent, polyphenylene sulfide and glass fiber molecules better, and the modified carbon nanotubes play the role of skeleton connection points, which further improves the impact strength of the polyphenylene sulfide composite material, thereby solving the problem of poor toughness and low impact strength of polyphenylene sulfide.

[0107] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A polyphenylene sulfide composite material, characterized in that: The method is composed of the following raw materials in parts by weight: 40-75 parts of polyphenylene sulfide, 15-30 parts of glass fiber, 3-10 parts of toughening agent, 3-8 parts of amino-terminated hyperbranched polyamide, and 0.5-1.4 parts of compatibilizer; The toughening agent is a core-shell structure, with modified carbon nanotubes as the core and low-density polyethylene as the shell; The compatibilizer is glycerol tri(1,2-epoxy)propyl ether and / or polyepoxy silicone oil; The preparation method of the toughening agent comprises the following steps: Hydroxylated carbon nanotubes are modified by using a terminal olefinic silane coupling agent to obtain modified carbon nanotubes, wherein the mass ratio of the terminal olefinic silane coupling agent to the hydroxylated carbon nanotubes is 1:(0.6-0.85); low-density polyethylene and the modified carbon nanotubes are mixed, melted, and extruded in a mass ratio of (2-5):1 to obtain a toughening agent.

2. A polyphenylene sulfide composite material according to claim 1, characterized in that: The mass ratio of the terminal olefin silane coupling agent to the hydroxylated carbon nanotube is 1:(0.7-0.8).

3. The polyphenylene sulfide composite material according to claim 1, characterized in that: The weight portion of the toughening agent is 5-7 parts.

4. The polyphenylene sulfide composite material according to claim 1, characterized in that: The weight portion of the compatibilizer is 0.7-1 part.

5. The polyphenylene sulfide composite material according to claim 1, characterized in that: The compatibilizer is polyepoxy silicone oil.

6. The polyphenylene sulfide composite material according to claim 1, characterized in that: The glass fiber is modified by a terminal epoxy silane coupling agent to obtain a modified glass fiber; the mass ratio of the terminal epoxy silane coupling agent to the glass fiber is (0.03-0.08):

1.

7. A polyphenylene sulfide composite material according to claim 6, characterized in that: The terminal epoxy silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

8. A method for preparing a polyphenylene sulfide composite material according to any one of claims 1 to 7, characterized in that: The steps include: The polyphenylene sulfide, glass fiber, toughening agent, amino-terminated hyperbranched polyamide and compatibilizer are mixed, melt-extruded and granulated to obtain a polyphenylene sulfide composite material.

Citation Information

Patent Citations

  • High strengthening and toughening type polyphenylene sulfide composite material and preparation method thereof

    CN109651814A

  • Thermoplastic resin-based conductive composite material and preparation method thereof

    CN112852138A

  • Polyarylene sulfide resin composition

    US5258450A